Dietary Zinc Requirement of Young Giant Gouramy (Osphronemus gouramy, Lac.) - Setiawati, Mia; Azwar, N.R.; Mokoginta, I.; Affandi, R. (Jurnal Akuakultur Indonesia, 2007)
This experiment was conducted to determine the dietary zinc requirement of young giant gouramy. Five experimental diets were used in this experiment containing iso-nitrogenous and iso-energy with different levels of zinc (0, 25, 50, 100, and 200 mg per kg). The initial means of body weight of body the fishes was 0.82 g per individual. The fishes were fed upon the diets at satiation, three times daily, for 12 weeks. The results indicated no zinc deficiency symptoms in this experiment. The daily growth rate, feed efficiency, survival rates and protein and lipid retention were not significantly different from all the diets. However, fish fed upon 25 mg Zn/kg diets produced the highest protein and total digestibility. The zinc contents of 25 mg Zn/kg diets gave the highest value in zinc accumulation in the bone, blood serum and eyes. The highest accumulation of the zinc in the liver occurred in 50 mg Zn/kg diets. There was increase in zinc content of the tissues after increasing levels of dietary zinc. Thus, Zn requirement for juvenile of giant gouramy was 25-50 mg/kg diets. Keywords: Osphronemus gouramy, Zinc, diet   ABSTRAK Penelitian ini dilakukan untuk mengetahui kebutuhan seng dalam pakan untuk benih ikan gurame.  Lima jenis pakan percobaan yang diuji mengandung iso-nitrogen dan iso-energi dengan kadar seng (Zn) yang berbeda (0, 25, 50, 100, and 200 mg per kg).  Bobot rata-rata benih yang digunakan adalah 0,82 g per ekor.  Ikan dipelihara selama 12 minggu dan diberi pakan 3 kali sehari.  Hasil penelitian menunjukkan bahwa tidak ada gejala defisiensi Zn.  Laju pertumbuhan harian, efisiensi pakan, kelangsungan hidup dan rentesi protein dan lemak tidak berbeda nyata untuk semua perlakuan.  Namun demikian, ikan yang diberi Zn sebanyak 25 mg/kg pakan menghasilkan kecernaan total dan protein tertinggi.  Perlakuan tersebut juga menghasilkan akumulasi Zn tertinggi dalam tulang, serum darah dan mata.  Akumulasi Zn tertinggi dalam hati diperoleh pada perlakuan 50 mg Zn/kg pakan.  Kandungan Zn dalam jaringan meningkat sejalan dengan meningkatnya kadar Zn dalam pakan. Dengan demikian, kebutuhan Zn bagi benih ikan gurame adalah sebanyak 25-50 mg /kg pakan. Kata kunci: Osphronemus gouramy, seng, pakan